Comparison of CIE94 and CIEDE2000 Color Difference Formulas Using Visual Shade Matching - Zeynep Demirekin; Erdal Eroglu; Mehmet Güven (Selcuk Dental Journal)
Background: Today, the frequency of seeking an aesthetic smile in patients who apply to dentistry clinics has increased compared to the past. This expectation is fundamental in restorations in the anterior region, as well as shape, size, and proportion, as well as color harmony. One of the most challenging stages in prosthetic dental treatment is to find the natural and correct color for the planned restorations. This study aims to examine the most commonly used visual color matching and color matching using Vita 3D Master color guide in terms of CIE94 and CIEDE2000 formulations in comparison and to examine the repeatability and reliability of the methods.